Effects of saddle height on anaerobic power production in cycling - Peveler, W. W.; Pounders, J. D.; Bishop, P. A. (The Journal of Strength and Conditioning Research, 2007)
In competitive cycling, setting the proper saddle height is important for both performance and injury prevention. This is also true for ergometer use in a laboratory. The cycling literature recommends using a 25-35= knee angle to set saddle height for injury prevention and recommends using 109 % of inseam length for optimal performance. Prior research has demonstrated that these 2 methods do not produce similar saddle heights. The purpose of this study was to determine if there is a difference in performance between these 2 methods. Trained cyclists (n = 9) and noncyclists (n = 18) participated in this study. Anaerobic power production was compared using a 30s Wingate protocol at a saddle height of 109 % of inseam and at 25 and 35° knee angles. Saddle height set using 109 % of inseam fell outside the recommended 25 to 35° knee angle 63 % of the time. There were no significant differences (p > 0.05) for peak power and mean power in either group between saddle heights. The data when using 109 % to set saddle height were then divided into those that fell within the recommended 25-35= knee angle and those that fell outside. A 25° knee angle produced a significantly higher mean power compared with 109 % in those that fell outside the recommended range. An increase in power, at a 25° angle, can be extrapolated to increased performance. There was no difference in performance detected in those individuals who fell within the recommended range. For this reason it is recommended that saddle height for cycles and ergometers be set using a 25-35° knee angle for both trained and untrained cyclists for both injury prevention and increased performance.